2015
DOI: 10.3855/jidc.5479
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytosis: a 16-year retrospective study in a metropolitan area in southern Brazil

Abstract: Introduction: Dermatophytoses are considered a public health problem. The objectives of this study were to determine the evolution of their prevalence in the metropolitan area of Porto Alegre, Brazil, and to analyze the dermatophyte species distribution according to body site and demographic characteristics of the patients. Methodology: This work was a retrospective analysis of data from patients attending a tertiary care hospital during 1996-2011. Results: There were 9,048 cases with cultures positive for der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
8
22
0
1
Order By: Relevance
“…Thus the two agents may have aggravated infectiousness accounting for greater number of cases. The anatomical site predilection is another determinant of the frequency with which various species are isolated [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the two agents may have aggravated infectiousness accounting for greater number of cases. The anatomical site predilection is another determinant of the frequency with which various species are isolated [16] .…”
Section: Discussionmentioning
confidence: 99%
“…T. violaceum was also the predominant cause of tinea capitis from similar Indian studies [7]- [9], [11] . M. gypseum is an uncommon geophilic fungus that has been reported as a cause of facial tinea from Brazil [16] . It has been isolated as soil saprophyte from Himachal [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data indicate that dermatophytoses are seen more frequently in developing countries and often associated with a history of exposure and the presence of risk factors . M. canis and M. gypseum are found frequently in tinea capitis and tinea corporis cases in both the American continent and Brazil …”
Section: Introductionmentioning
confidence: 99%
“…A study in the US revealed that between 22% and 55% had hair scalp infection of dermatophytes [9]. Another study conducted in Brazil showed that Trichophyton rubrum , Microsporum canis , and Epidermophyton floccosum were the most prevalent species infecting humans in developing countries [10]. The World Health Organization estimated that dermatophytes affect about 25% of the world population [6].…”
Section: Introductionmentioning
confidence: 99%